Specification of Uneven Location by the Bound Resonance of Skin Substance on the Roll Transformation Realization System - lae Kim, Jeong; ju Kim, Hye; young Lee, Kee (International Journal of Engineering and Technology, 2018)
Bound transformation technology is constructed the resonance status for point-ring pattern of the glimmer realization rate (GRR) and distinction realization rate (DRR) on the bound realization gestalt. The realization rate condition by the bound realization gestalt is associated with the roll resonance system.  As to check up on a point-ring pattern of the uneven transformation, we are constructed of the bound value with bound layer point by the roll-close-up structure on the skin substance. The concept of realization rate is made sure of the reference of glimmer rate and distinction rate for transformation signal by the bound resonance gestalt. Moreover to appear a uneven transformation of the GRR-DRR of the medium in terms of the bound-resonance gestalt, and bound point resonance that is to get the a bound value of the far transformation of the Wa-rm-FA-μAVG-MIN with 8.27±1.57 units, that was the a bound value of the convenient transformation of the Wa-rm-CO-μAVG-MIN with 3.43±0.01 units, that was the a bound value of the flank transformation of the Wa-rm-FL-μAVG-MIN with 1.06±0.50 units, that was the a bound value of the vicinage transformation of the Wa-rm-VI-μAVG-MIN with 0.21±0.07 units. The roll resonance will be to compute at the ability of the bound-resonance gestalt for the control degree realization rate on the GRR-DRR that is delimited the uneven glimmer and distinction gestalt by the realization rate system. Roll realization system will be supposition of a gestalt by the special signal and to count a bound data of roll resonance rate.